Essentials of petroleum : a key to oil economics - Frankel, Paul H. (London : Frank Cass, 1969)
Part 1 of this text examines Oil and public opinion. Part 2 describes the economics of a liquid. Part 3 focuses on price structure. Part 4 examines the shape of the industry. Finally, part 5 discusses policies for the industry.
Includes bibliographical references and index.
ne 21/01/2019
Loans
Keywords: Petroleum industry and trade